Possibilities and challenges of collaborative teaching networks between university and school: a multi-case study - Almudena Ocaña-Fernández; Analía E. Leite-Méndez; José L. Del Río-Fernández; Virgina Martagón-Vázquez (Revista Latinoamericana de Tecnología Educativa)
This article presents the main findings of a multi-case study carried out within the framework of a research project on collaborative networks in education, the aim of which is to gain an in-depth understanding of some experiences aimed at generating inclusive, horizontal and transdisciplinary spaces for dialogue, reflection and collaboration in the design and implementation of pedagogical practices from a critical perspective. This networked, dialogical and participatory research enables the transfer of the results beyond the academic sphere and has an impact on the process of progress and improvement of the centres and teachers involved. From a qualitative, comprehensive and participatory methodological approach, we proceed to analyse various educational scenarios which, despite idiosyncratic differences, share an interest in generating pedagogical knowledge in a collaborative and democratic way. From this perspective, three case studies are presented that reflect university-school collaboration through the implementation of different initiatives in learning communities, pedagogical laboratories and rural contexts. The results obtained show that the construction of networks promotes the exchange of knowledge, the strengthening of links between institutions and the possibility of moving towards other educational models that are more democratic, dialogic, inclusive, critical and committed to social change.